Cellular and Molecular Targets of Menthol Actions - Oz, Murat; El Nebrisi, Eslam G.; Yang, Keun-Hang S.; Howarth, Frank C.; Al Kury, Lina T. (Frontiers in Pharmacology, 2017)
Menthol belongs to monoterpene class of a structurally diverse group of phytochemicals found in plant-derived essential oils. Menthol is widely used in oral hygiene products, confectionary, pharmaceuticals, cosmetics, pesticides, and as a flavoring agent. In addition, menthol has been reported to have anti-inflammatory and analgesic actions. In recent years, there has been an increasing interest in understanding the pharmacological actions of menthol. TRP channels have been demonstrated to mediate the cooling actions of menthol. There is also evidence indicating that menthol can modulate the functional properties of several types of voltage and ligand-gated ion channels, suggesting that some of its pharmacological actions may be mediated by alterations in cellular excitability. In this report, we review the literature relating the interaction of menthol with voltage and ligand-gated ion channels.